1970
DOI: 10.1002/anie.197001241
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Solvation Shell of Dissolved Particles

Abstract: The first part of the article deals with the structure of the solvation shell of simple ions, particularly those wifh the inert gas strgcture, in aqueous and non-aqueous solution. It is nowadays possible in favorable cases, to determine the solvation number or the coordination number in the first sphere. The solvation shells appear to be "more liquid'' than was formerly believed. The hydration of neutral inert particles in aqueous solution is discussed in the second part. Caution is advised in the postulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1971
1971
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(10 citation statements)
references
References 148 publications
0
10
0
Order By: Relevance
“…45 years ago Hertz & An suggested that water molecules restructure even around inert NPs (Hertz, 1970). The difficulty of discerning the interfacial signal from the bulk solvent prevented its experimental validation for a long time.…”
Section: Solvent Restructuring Around Nanoparticles and Shortrange Ordermentioning
confidence: 99%
“…45 years ago Hertz & An suggested that water molecules restructure even around inert NPs (Hertz, 1970). The difficulty of discerning the interfacial signal from the bulk solvent prevented its experimental validation for a long time.…”
Section: Solvent Restructuring Around Nanoparticles and Shortrange Ordermentioning
confidence: 99%
“…Therefore, comparing Equations 31 and 30, AG,-0 = AGps 0 /n -RT ln [(n + 1 -i)/i] (32) or in the form of equilibrium constants (33) be formulated as the weighted average of the chemical shifts arising from all possible arrangements of solvent around the ion (13). Hence, if the ith species has an intrinsic shift of 6t, the observed shift 6 is given by…”
Section: Thusmentioning
confidence: 98%
“…Adopting the mole fraction scale and introducing standard chemical po- Equation 13 is Equation 4 of the previously given treatment (3) and derived there by an alternative but equivalent method (noting that w° + p° = 55.5 if an aquamolality scale is adopted as henceforth). It is also similar to GBK's Equation 53.…”
Section: Basic Thermodynamic Treatmentmentioning
confidence: 99%
“…Here r is the capillary radius (cm), u the surface tension h = 2u/dgr (9) (dyn/cm), d the density (g/cm3), g the acceleration due to gravity (980.66 cm/s2), and h the capillary rise (cm). Using the cited sources of u for the standards, the respective values of r computed were 0.05334, 0.05320, 0.05266, 0.05308, 0.05281, and 0.05283 cm.…”
Section: -mentioning
confidence: 99%